Social Representation of Women in Buchi Emecheta’s The Joys of Motherhood and Flora Nwapa’s Efuru - GBAGUIDI, Célestin (Advances in Social Sciences Research Journal, 2022)
An analysis of the African fiction in the South of the Sahara shows a bias in the depiction of male and female characters. The purpose of this article is to explore the social representation of African women in post-colonial Africa as hardworking and intrepid characters, man’s companion, support and shield, and eventually as educators. Contrary to the distorted social perception society has of women in Africa, female novelists like Buchi Emecheta in The Joys of Motherhood and Flora Nwapa through Efuru, have deconstructed the social established norms giving masculine roles to their female characters. Nnu Ego, Adaku and Efuru – characters in these novels – have reversed the roles by working hard, protecting their families and by educating children and societies. Through the use of post-colonial criticism as backdrop, this paper deconstructs the negative representations that patriarchal societies have of women highlighting the predominant roles that female characters play. A qualitative data analysis and feminism approaches have been used to better explore the social representation of women in African patriarchal settings in this work.